Bats (chiropteran) reported with Aspergillus species from Kubah National Park, Sarawak, Malaysia. - Sathiya Seelan, Jaya Seelan; Anwarali, F. A.; Muid, Sepiah; M.T, Abdullah (Universiti Malaysia Sarawak, (UNIMAS), 2008)
A preliminary survey of chiropterans (bats) with potential zoonotic fungi was conducted as part of the Sowell-UNIMAS Expedition 2006. This survey was conducted at Kubah National Park, Matang, Sarawak from 14th to 16th August 2006. The main aim of this survey was to document variety of fungal isolates from bats external (ears) and internal (saliva and anal) swabs. All of the fungi species were subjected to both macroscopic and microscopic observations to characterize their morphology. Out of 23 species of bats observed, 13 (56.5%) species were found to contain 17 fungi isolates of the genus Aspergillus from five subgenera, five sections and six species. The fungi isolates were Aspergillus restrictus, A. sydowii, A. fumigatus, A. niger, A. clavatus and A. japonicus. The highest numbers of isolates recorded was for A. restrictus with six isolates followed by A. fumigatus and A. sydowii with two isolates respectively. Where as, A. niger, A. clavatus and A. japonicus each recorded with one isolate only. Aspergillus fumigatus was the first record isolated from bats the samples (n = 64) from Sarawak. It was reported that this isolate is a pathogenic and thermophilic (able to grow up to 65°C) isolate which was found to be on a lesion near ear opening of Hipposideros cervinus. Further work should be done to discover potential mycoflora in wildlife mammals.